Evaluation of the accuracy and precision of the microlab 300 device for total cholesterol test on the CHOD-PAP method - Ananda, Fanny Rizki; Sungkawa, Hendra Budi; Kamilla, Laila; Fatayati, Imma (ELECTRON (Journal of Science and Technology), 2025)
Internal quality assurance (PMI) is a routine preventive and monitoring activity in the laboratory to minimize errors and produce accurate tests. Quality accuracy and precision are important indicators in assessing PMI. Accuracy indicates the closeness of the test results to the true value, while precision describes the closeness of the results of repeated tests on the same sample. Total cholesterol examination using a spectrophotometer, especially the CHOD-PAP method, is often carried out at the Clinical Laboratory of the Poltekkes Kemenkes Pontianak due to its stability. This observational study aims to evaluate the accuracy and precision of the Microlab 300 tool for total cholesterol examination using the CHOD-PAP method at the Integrated Laboratory of the Poltekkes Kemenkes Pontianak. The study population was the assayed control serum solution, with samples in the form of normal control serum solution dialab which was divided into 100 vials containing 50 µL. A total of 30 vials were used for the preliminary period and 30 vials for the control period. The parameter examined was total cholesterol by CHOD-PAP method. The results showed the average accuracy of the Microlab 300 tool was 96.08% and precision was 99.21%. The daily graph using Westgard's rule shows that the control material is within the control limits. Thus, it can be concluded that the Microlab 300 tool shows good accuracy and precision in the examination of total cholesterol CHOD-PAP method in the laboratory